Ressoadores e guias dielétricos cilíndricos operando em micro-ondas e óptica: antenas dielétricas e acopladores refletores de Bragg a fibra - Rocha, Hélio Henrique Barbosa (2010)
Two heterogeneous contributions to modern communication systems – although fully possible to be correlated – are presented. The first one deals with resonant antennas consisting of new dielectric ceramics based on Fe2O3. These materials characterized at microwave frequency range possess low relative permittivity, low loss tangent and, concerned with the monophasic samples, negative temperature coefficient of resonant frequency. Subsequently, the cylindrical dielectric resonator antennas (CDRAs) supported on rectangular ground plane and fed by monopole are analyzed according to the following radiation performance criteria: resonant frequency, input impedance, bandwidth and radiation patterns. Besides experimentation, the study involved computational procedure, so that the results of both can be compared. A commercial software based on the finite element method was employed to examine the CDRAs. It follows that as higher is the permittivity of a material, the lower are the frequency at which it resonates as well as its bandwidth. Satisfactory impedance matching and broadside radiation patterns are observed, what enables the materials investigated to this relevant application. Additionally, the stacking of the monophasic CDRAs prototypes resulted in bandwidth enhancement, presumably due to their excited high order modes. The second contribution focuses on dielectric waveguides operating at optical frequencies, being fiber Bragg grating couplers (FBGCs) investigated in this scenario. Indeed, they result from a combination of two versatile and widely applied devices: fiber Bragg gratings and directional couplers. Two numerical case studies related to the interaction between optical signals and structures were performed. The theoretical model observed is based on the coupled mode theory since it provides a satisfactorily accurate description of the devices optical properties. By the way, the theoretical model is coded in FORTRAN programming language according to a predictor-corrector algorithm. In terms of operational power levels, analyses are carried out in frequency and (mainly) time domains. Under specific conditions, the capability of the extraction, reshaping and switching of pulses – examples of essential functions for all-optical processing – reinforces the importance of such hybrid structures.